Evaluation of the Effect of a Swimming Training Program on Levels of Lung Hypoxia Inducible Factor-1α (HIF-1α) in Pups - Shadmehr Mirdar; Ana Arab; mahdi Hedayati; akbar Hajizadeh (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2013)
Background and Objectives: Cadmium is one of the most important biological contaminants that its intake in pregnancy causes disease and malformation s in the mother and baby. This study was done with the aim of evaluating the effect of maternal regular swimming training and oral cadmium intake during pregnancy on the levels of lung hypoxia inducible factor-1α (HIF-1α) in pups.   Methods: In this study, 32 female wistar rats weighting 200±20g, after 2 weeks of familiarity with the new environment and pregnancy were divided into four groups of 8, including: 1- cadmium, 2- swimming, 3- cadmium-swimming, and 4- control. Swimming training started from the first day of pregnancy and continued once a day (5 days per week) until delivery day. Intake dose of cadmium was 400mg/l in drinking water. HIF-1α concentration of Lung was determined with enzyme-linked immunosorbent assay (ELISA) method. The data were analyzed by one-way analysis of variance and Holm-Sidak tests at significance level of p<0.05.   Results: The mean weight of pups in cadmium group showed a significant decrease (p<0.001) compared to the control group. Also, the pups' lung HIF-1α levels significantly (p<0.001) increased in the swimming group and significantly (p<0.001) reduced in cadmium group compared to control group.   Conclusion: These results indicated the effect of swimming training on the increase of lung HIF-1α levels in pups that their mothers were swimming regularly in pregnancy. Accordingly, it seems submaximal swimming training in pregnancy can modify its negative effects on the fetal lungs through compensating of cadmium-induced decrease in HIF-1α.